Management of chronic hepatitis B before and after liver transplantation. Issue 1 (14th February 2017) - Wang, B; Agarwal, K; Joshi, D
Abstract : Chronic hepatitis B infection is a global public health problem associated with significant morbidity and mortality. Persistent infection may evolve to liver cirrhosis and hepatocellular carcinoma, and hepatitis B-related liver disease is a common indication for liver transplantation. Patients with advanced liver disease should be treated with antiviral therapy which may result in clinical improvement. The management of patients after liver transplant then focuses on preventing hepatitis B recurrence in the graft. With the introduction of prophylactic treatment, patient and graft survival has improved significantly. In this review, we will discuss the management of patients with hepatitis B-related cirrhosis, both compensated and decompensated. We also review the management of hepatitis B after liver transplantation.